Performance metrics and required returns for UK real estate development schemes. Issue 2 (2nd April 2020) - Crosby, Neil; Devaney, Steven; Wyatt, Pete
ABSTRACT: Real estate development has received less scrutiny than real estate investment in terms of appraisal practices and performance measurement. This is despite the inherent uncertainty and financial risks associated with development as an activity. We investigate market practices regarding performance metrics and return expectations both for residential and commercial real estate development in the UK, exploring what is considered as an appropriate return and how this varies according to type and duration of scheme, and method of appraisal used. After examining the literature and the information available on ex-post returns from development activity, results from a survey of real estate developers are reported, supplemented by findings from interviews. The results suggest that the use of traditional residual valuation techniques dominates discounted cash flow models when appraising development projects, particularly among residential developers, while profit-on-cost and profit-on-value are the most popular metrics for quantifying required returns. Unlike NPV or IRR, these metrics do not account for the timing of cash flows, raising questions about the robustness of appraisals in this sector. Such metrics might suffice if required profits are adjusted in ways that are consistent with scheme duration and risks, but it is unclear that this is currently the case.